Performing Dual Gender: Female Characters’ Masculine and Feminine Acts in Birds of Prey (2020) - Muhammad Reza Pahlevi; Ephrilia Noor Fitriana (Jurnal Ragam Pengabdian, 2026)
This research will explore how is dual gender performativity depicted in female characters and how does dual gender performativity influence them to face the injustices situation in the film Birds of Prey (2020) by the female characters: Harley Quinn, Renee Montoya, Black Canary, Helena Bertinelli, and Cassandra Cain. This research analyzes the film by visual and textual from selected scenes. The visual includes something that appears and visible, such as: facial expressions, gestures, body languages, clothes, makeup, fashion, and action. Meanwhile the textual data comes from a dialoge that is spoken by the female characters to support the visual aspects. This research uses gender performativity theory by Judith Butler to deeply analyze. The result shows that society has a big role to set the standards and as a human, especially women must be able to stand on their own feet to face the injustices. Dual gender performativity divided into masculine act and feminine act which is marked with something that they wear, visible and also from the characters‟ dialogue to strengthen the findings by Butler‟s approaches.